Efektivitas Model Pembelajaran Example Non Example, Picture and Picture dan Problem Based Learning Terhadap Pemahaman Konsep Siswa - Thofil Nubatonis; Nonci Melinda Uki; Marince Inforsalina Leo (Quagga : Jurnal Pendidikan dan Biologi, 2022)
Tujuan penelitian ini untuk mengetahui efektifitas Model Pembelajaran Picture and Picture, Example Non Example dan Problem Based Learning Terhadap Pemahaman Konsep Siswa. Metode yang digunakan adalah Quasi Experimental dengan desain  eksperiment pola M-G (matched group design) yang melibatkan tiga kelas. Data dikumpulkan melalui tes hasil belajar dan di analisis menggunakan uji Anova Satu jalur. Hasil penelitian menunjukkan bahwa pemahaman konsep siswa kelas example non example (Rata-rata 81.52), kelas picture and picture (rata-rata 86.47), kelas PBL (rata-rata 76.64), maka dapat di simpulkan bahwa model pembelajaran Picture and picture efektif untuk meningkatkan pemahaman konsep siswa. Peningkatan pemahaman konsep siswa dibuktikan dengan analisis gain yang menunjukkan model pembelajaran example non example (rata-rata 0.69 kriteria sedang), picture and picture (rata-rata 0.86 kriteria tinggi) dan PBL (rata-rata 0.67 kriteria sedang). Hal ini menunjukkan bahwa penggunaan model pembelajaran Picture and picture efektif untuk meningkatkan pemahaman konsep siswa dilihat dari kriteria N-Gain.  This study aims at knowing the effectiveness of Example Non Example, Picture And Picture and Problem Based Learning (PBL) model towards students’ concept understanding. Quasi Experimental with Nonequivalent Control Group Design was used as the method by involving three classes, consisting of Example Non Example class, Picture and Picture class, and PBL class. The data were gathered from test and were analyzed using One Way Anova. The result shows that students’ concept understanding in Example Non Example class is 81.52 in the average, Picture and Picture Class is 86.47 in the average, and PBL class is 76.64 in the average. Hence it can be concluded that Picture and Picture learning model is effective to improve students’ concept understanding. The improvement of students’ concept understanding is proven with Gain Analysis which shows that Example Non Example learning model is on medium criterion with average score 0.69, picture and picture learning model is on high criterion with average score 0.86, and PBL model is on medium criterion with average score 0.67. This result shows that based on N-Gain criterion score, the application of Picture and picture learning model is effective to improve students’ concept understanding.